2012
DOI: 10.1139/b2012-093
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of ethylene in programmed cell death and climacteric-like behaviour during the remodelling of lace plant (Aponogeton madagascariensis) leaves

Abstract: Programmed cell death (PCD) plays an important role in several plant developmental processes. The phytohormone ethylene has been implicated in PCD signalling in many plant systems, but it is also important in developmental processes such as seed germination, flowering, and climacteric fruit ripening. Lace plant (Aponogeton madagascariensis (Mirbel) H. Bruggen) is an aquatic monocot that develops perforated leaves via the deletion of cells through developmentally regulated PCD. The plant is ideal for studying P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…We found that ethylene-response factor (ERF) genes and genes required for JA biosynthesis, such 12-oxophytodienoate reductase (OPR2) gene, and involved in controlling JA responses, such jasmonate ZIM-Domain 1 gene (JAZ1), were overrepresented in the 1st outer scale and may have crucial role in skin formation in the outer scales ( Figure 7 ; Table 2 ). Ethylene is involved in developmental processes that employ PCD such as senescence (Graham et al, 2012), perforation formation in the lace plant (Dauphinee et al, 2012) and in maize endosperm development (Young et al, 1997). …”
Section: Discussionmentioning
confidence: 99%
“…We found that ethylene-response factor (ERF) genes and genes required for JA biosynthesis, such 12-oxophytodienoate reductase (OPR2) gene, and involved in controlling JA responses, such jasmonate ZIM-Domain 1 gene (JAZ1), were overrepresented in the 1st outer scale and may have crucial role in skin formation in the outer scales ( Figure 7 ; Table 2 ). Ethylene is involved in developmental processes that employ PCD such as senescence (Graham et al, 2012), perforation formation in the lace plant (Dauphinee et al, 2012) and in maize endosperm development (Young et al, 1997). …”
Section: Discussionmentioning
confidence: 99%
“…Recent research shows ethylene is involved in regulation of PCD in lace plant during perforation formation and senescence, in a climacteric-like pattern (Dauphinee et al 2012 ). They showed that ethylene production peaks during the window and senescence stages, both in-which PCD is occurring.…”
Section: Discussionmentioning
confidence: 99%
“…In plants, several genetic components have been associated with PCD: these include receptor-like/Pelle kinases, pattern recognition receptors, stress receptors, reactive oxygen (ROS) sensors, MAPK cascade, hormonal regulators, transcription factors and caspase-like enzymes [reviewed in Rantong and Gunawardena ( 2015 )]. Hormones involved in plant PCD include, but are not limited to salicylic acid (Cao et al 1994 ; Mur et al 2013 ), jasmonic acid (Mur et al 2013 ), and ethylene (Zhao and Schaller 2004 ; Dauphinee et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations